(untitled) (Polis (Santiago), 2018)
A high rate of mental illness is very common among university students. The challenges encountered in academic life, especially in graduate school, put the mental health of students to the test, leading many of them to develop mental disorders. This article presents both a literature review and empirical research that analyze aspects of the mental health of 2,903 postgraduate students from all over Brazil. The results show that 74% of respondents have anxiety, 31% insomnia and 25% depression. The study also showed that most of them suffer constantly with a sleep related disorder, such as: difficulty falling asleep (39%), feeling guilty at bedtime (39%), waking up several times during sleep periods (30%), or waking up in the middle of sleep and not being able to fall asleep again (20%).